Effects of the Replacement of Dietary Fishmeal by the Blend of Tenebrio molitor Meal, Chlorella Meal, Clostridium Autoethanogenum Protein, and Cottonseed Protein Concentrate on Growth, Protein Utilization, and Intestinal Health of Gibel Carp (Carassius gibelio, CAS Ⅴ) - Yongning Yu; Xing Wang; Junyan Jin; Dong Han; Xiaoming Zhu; Haokun Liu; Zhimin Zhang; Yunxia Yang; Shouqi Xie (Aquaculture Nutrition)
The trial was conducted to investigate the effects of the replacement of dietary fishmeal (FM) by the blend of Tenebrio molitor meal (TMM), Chlorella meal (CM), Clostridium autoethanogenum protein (CAP), cottonseed protein concentrate (CPC) on growth, protein utilization and intestinal health of gibel carp (Carassius gibelio, CAS Ⅴ). The FM-based diet was used as the control, and the blended proteins (TMM: CM: CAP: CPC) at ratios of 1 : 1:8 : 2 (BLEND A), 1 : 1:6 : 4 (BLEND B), and 1 : 1:4 : 6 (BLEND C) were used to replace FM at three levels (33%, 67%, 100%), respectively. The results showed that, compared to the control group, growth performance increased significantly when dietary FM was fully replaced by BLEND B (P<0.05), while decreased by BLEND A (P<0.05). The complete substitution of FM with BLEND B significantly upregulated the mRNA expression of intestinal proinflammatory cytokines, anti-inflammatory cytokines, and tight junction-related genes (P<0.05), improving intestinal tissue morphology and health. And it also significantly increased intestinal trypsin activity (P<0.05), upregulated the mRNA expression of amino acid sensory receptor-related and amino acid or peptide transport-related genes (P<0.05), increased protein apparent digestibility coefficient (P<0.05). The 100% substitution of FM with BLEND A significantly upregulated the mRNA expression of intestinal proinflammatory cytokines and downregulated the mRNA expression of anti-inflammatory cytokine il-10 (P <0.05), reduced intestinal villus height (P<0.05), and decreased protein apparent digestibility coefficient (P<0.05). In conclusion, BLEND B could completely substitute dietary FM and was beneficial to the growth and health of gibel carp. Dietary digestible essential amino acids index (DEEAI) was found as an important indicator and should be higher than 79.5% to meet the maximum growth of fish.